Pelatihan Pelaksanaan Kurikulum Merdeka Belajar Pada Pengelolaan Kelas Rangkap Di Sekolah Dasar - Wahira Siruwa; Andi Mappincara; Hasan Hasan (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
The Community Partnership Program for elementary school teachers is carried out in the form of training activities to implement the independent learning curriculum for elementary school teachers. This activity aims to provide understanding for teachers, especially the independent learning curriculum in multigrade management. This training activity uses lecture, question and answer, and discussion methods. The trainees are elementary school teachers. The results of the training showed that elementary school teachers could understand and understand the material given in the activity with the average results of the excellent category before training and the superb type after training because the training material is equipped with exercises in understanding the implementation of the independent learning curriculum in multigrade management so that teacher obstacles in implementing the independent learning curriculum in schools can be overcome.